2014
DOI: 10.1177/0956797614530725
|View full text |Cite
|
Sign up to set email alerts
|

A Perceptually Completed Whole Is Less Than the Sum of Its Parts

Abstract: How efficiently do we integrate across the disconnected image fragments that fall upon our eyes when we view partly occluded objects? We used a psychophysical summation-at-threshold technique to address this question by measuring discrimination performance with both isolated and combined features of physically fragmented but perceptually complete objects. If visual completion promotes superior integration efficiency, we would expect performance with a visually completed object to exceed what would simply be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In contrast, if showing the features in combination leads to a decrement in processing efficiency, the sensitivity for the combination should be less than the summed sensitivities across individual features (i.e., "sub-optimal" integration). Surprisingly, Gold (2014) found that integration efficiency was significantly suboptimal in all three tasks-a result that indicates there are hidden costs to the process of visual completion and is consistent with our current findings that perceptual organization can actually lead to significant reductions in overall processing efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, if showing the features in combination leads to a decrement in processing efficiency, the sensitivity for the combination should be less than the summed sensitivities across individual features (i.e., "sub-optimal" integration). Surprisingly, Gold (2014) found that integration efficiency was significantly suboptimal in all three tasks-a result that indicates there are hidden costs to the process of visual completion and is consistent with our current findings that perceptual organization can actually lead to significant reductions in overall processing efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Schwarz and Miller (2014) discuss the interactive versus independent effects of redundant signals on response accuracy, recommending that both hits and false alarms be considered with equal rigor in any analysis. In the realm of perceptual sensitivity at threshold, researchers have applied the statistical logic of Miller's RMI to study the perception of facial expressions based on single features and combinations of features (Gold, 2014). These measures also seem ripe for use by researchers of collaborative cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The facilitatory component of the Bregman-Kanizsa effect could be considered as a kind of configural superiority effect. However, Gold (2014) provided evidence that visual completion processes involve unanticipated costs. He found that discrimination sensitivity is higher when targets are perceived as isolated fragments than as parts of a whole including either MC (Bent Bars condition) or AC (Rotating Squares and Shrinking/Expanding Squares conditions).…”
Section: The Bregman-kanizsa Effectmentioning
confidence: 99%